Два множества решений: х=(-1)^k*(pi/3)+pi*k или х=pi/2+2pi*k
k -любое целое
Объяснение:
cos(pi/2-x)=sinx=у
Имеем у^2-(1+sqrt(3)/2)+e+sqrt(3)/2=0
по теореме Виета два решения у=1 и у=sqrt(3)/2
Вспомнив обозначение, получим для у=sqrt(3)/2= sinx
х=(-1)^k*(pi/3)+pi*k
но и для у=1 (sinx=1)
х=pi/2+2pi*k
Два множества решений: х=(-1)^k*(pi/3)+pi*k или х=pi/2+2pi*k
k -любое целое
Объяснение:
cos(pi/2-x)=sinx=у
Имеем у^2-(1+sqrt(3)/2)+e+sqrt(3)/2=0
по теореме Виета два решения у=1 и у=sqrt(3)/2
Вспомнив обозначение, получим для у=sqrt(3)/2= sinx
х=(-1)^k*(pi/3)+pi*k
но и для у=1 (sinx=1)
х=pi/2+2pi*k